Always room for one more - Leodhas, Sorche Nic 1898-; Hogrogian, Nonny (New York Holt, Rinehart and Winston, 1965)
In this Scottish folk song, a generous family always has room for another person and invites in everyone who passes by.
Children's story based on the Scottish ballad of the same title.
"Note about the song" (with music): p. [30]-[31]
Keywords: Folk songs, English -- Texts. -- Scotland; Folk songs -- Scotland